Ribavirin Improves NK Cell IFNγ Response During Sofosbuvir-based DAA Therapy in HCV-infected Liver Transplant Recipients. Issue 10 (1st October 2021) - Adenugba, Akinbami; Hornung, Matthias; Weigand, Kilian; Peschel, Georg; Junger, Henrik; Kupke, Paul; Lang, Hauke; Marquardt, Jens U.; Zimmermann, Tim; Geissler, Edward K.; Schlitt, Hans J.; Werner, Jens M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Chronic hepatitis C virus (HCV) infection is characterized by activation of natural killer (NK) cells. Here, we asked whether HCV elimination by sofosbuvir-based direct-acting antivirals (DAAs) and the addition of ribavirin (RBV) improve NK cell function in liver transplant (LTx) recipients. Methods: We analyzed NK cell degranulation and interferon (IFN)γ-response along with STAT1 and STAT4 phosphorylation in 29 HCV-infected LTx recipients and 17 HCV-infected patients during DAA treatment. Results: Compared with uninfected LTx recipients, NK cells from HCV-infected LTx recipients were polarized toward cytotoxicity with increased CD107a-degranulation (10.1% versus 14.6%; P = 0.0263) and reduced capacity to produce IFNγ (43.0% versus 26.7%; P = 0.0002). The altered phenotype of NK cells in HCV-infected LTx recipients was accompanied by increased STAT1 (44.6% versus 87.4%; P < 0.0001) and STAT1 phosphorylation (0.7% versus 8.9%; P = 0.0005) compared with pSTAT4 IFNα-induction (29.9% versus 17.6%; P = 0.0014). Successful DAA therapy did not affect CD107a-degranulation but decreased STAT1. RBV cotreatment with DAA therapy for HCV increased CD56 Bright NK cell IFNγ-responses in LTx recipients (70.9% versus 89.2%; P = 0.002), and this correlated to an increase in the inducibility of pSTAT4 (MFI 157 versus 173; P = 0.0002). Conclusions: RBV cotreatment of HCV infection improved pSTAT4-dependent IFNγ-production in NK cells. This is relevant especially for immunocompromised patients such as LTx recipients or patients with end-stage liver disease.